PELATIHAN APLIKASI BANK SAMPAH BERBASIS WEB PADA BANK SAMPAH BERKAH SEJAHTERA DESA RAWA PANJANG - Hendradi, Prionggo; Kurniawan, Wawan; Dewi, Yusriani Sapta; Kusumawati, Kiki; Nurhayati, Nurhayati; Chafid, Nurul (Jurnal AbdiMas Nusa Mandiri, 2025)
At Berkah Sejahtera Waste Bank, the service process is still carried out manually, namely by recording in the waste bank book so that data accuracy and timeliness often have errors in management. To find solutions to existing problems, it is necessary to have a computerized data management system in a waste bank institution as an effort to accelerate the processing of waste bank management transaction data that can provide convenience in carrying out transaction activities, managing Berkah Sejahtera Waste Bank savings, and creating transparency and accountability in the Berkah Sejahtera waste bank management unit in the Rawa Panjang Village area, Bojong Gede, Kabupaten Bogor. The applied method includes partner needs analysis, development of a digital waste bank application, training on application usage, and evaluation of the training outcomes. This application training activity was attended by 34 participants consisting of representatives of the management, and customers of the Berkah Sejahtera Waste Bank. The result of this training is an increase in the usefulness of training by 88% and feedback in using the E-BAS application recorded at 91.18% This waste bank application is a web-based data processing that can speed up and facilitate Waste Bank officers in conducting transactions, processing customer savings data, updated, transparent, and informative information and can be accessed at any time.